Website IoCNS for Increasing Parent’s Knowledge about Nutrients of Children - Rizona, Firnaliza; Citra, Viona Fracellia; Appulembang, Yeni Anna; Rahmawati, Fuji (Indonesian Journal of Global Health Research, 2024)
The world is currently facing a double burden of child nutrition problems. Prevention of imbal-anced nutrition in school age chil-dren can be achieved through changes in children's behavior such as consuming balanced nutrition intake, increasing appropriate physical activity and reducing con-sumption of unhealthy snacks. However, not only children but also parents don’t know whether their children are risk of nutrition imbalance from various un-healthy behaviors. Objective: The aim of this research was to know the effect of Web-site Information of Children’s Nutritional Sta-tus for increasing par-ent’s knowledge. Method: This research was quantitative research which used pre-experimental with one group pre and posttest design. The re-spondent was 20 parents of the students in elementary school. The data was collected by using questioner after conducting in-tervention using website. Results: The statistic result with Wilcoxon test showed im-proving par-ent’s knowledge with the result p=0,001. Conclusions: Using media education based on digital such as the website has an impact on increasing parental knowledge of child nutrition.